Continuous Electrophoretic Deposition and Electrophoretic Mobility of Ligand-Free, Metal Nanoparticles in Liquid Flow. Issue 4 (1st January 2015) - Koenen, Sven; Streubel, René; Jakobi, Jurij; Schwabe, Kerstin; Krauss, Joachim K.; Barcikowski, Stephan
Abstract : Direct current electrophoretic deposition (DC-EPD) of ligand-free metal nanoparticles in a flow-through reactor is studied by analyzing the educt colloid and the outflow of the flow through chamber while the concentration of the colloid and the strength of the electric field is varied. Metal nanoparticles synthesized by pulsed laser ablation in liquid (PLAL) are used to ensure that the colloidal nanoparticle surface is free of any ligands and that the colloid's stability and movement in an electric field is solely influenced by electrostatic forces. Electrophoretic mobility and deposition kinetics of these ligand-free nanoparticles on plain surfaces are examined for different electric field strengths. Additionally, a continuous liquid flow DC-EPD process is presented and optimized regarding deposition rate, colloid stability, and liquid flow rate. The reported parameter window for high deposition rates of nanoparticles without a negative impact on the colloid, allows to define an efficient stationary EPD process suitable for high throughput applications.